The Implementation Of Discussion In Teaching ReadingAt Seventh Grade Of Smp Murni 1 Surakarta Year 2015 - Nuary, Cynde; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
This study aims at describing 1) the implementation of discussion in teaching reading at seventh greade of SMP Murni 1 Surakarta, 2) the problems faced by the teacher in implementing discussion in teaching reading at seventh grade of SMP Murni 1 Surakarta year 2015. In achieving the objectives, the researcher used descriptive qualitative as an approach to collect and analyze the data. The researcher gets the data of the research from event, informant and document. The method of collecting data are observation, interview and documentation. The method of analysis data are data reduction, data display, conclusion and verification. The researcher found the result of the research. 1) The process of discussion are follows: pre-discussion activities, whilst discussion activities and post discussion activities. The kinds of discussion are (a) discussion-based teaching (b) small group discussion (c) classroom discussion. 2) The problem faced by the teacher in implementing the technique are the techniques, classroom management, timing management, and the students. The researcher gets solution to solve the problem faced by the teacher in implementing the discussion in teaching reading at seventh grade of SMP Murni 1Surakarta. There are: (a) the teacher should have interaction with the students and often gives motivations to the students. (b) the teacher should pay more attention to the students in discussion process, especially in whilst discussion. (c) the teacher must have variety of tehniques to solve the problem faced.